The effectiveness of peer support from a person with lived experience of mental health challenges for young people with anxiety and depression: a systematic review - Magenta B. Simmons; Sharla Cartner; Roxxanne MacDonald; Sarah Whitson; Alan Bailey; Ellie Brown (BMC Psychiatry, 2023)
Abstract Background Peer workers support individuals experiencing mental health challenges by drawing on their shared lived experience. Peer support has become increasingly popular for young people with anxiety and depression, but the evidence base is unclear. This systematic review aimed to understand the effectiveness of peer support for youth depression and anxiety (either primary or comorbid), and to understand in which contexts, for whom, and why peer support works. Methods A systematic search was conducted with the Orygen Evidence Finder, Embase, MEDLINE, and PsycInfo from January 1980 to July 2022. Controlled trials of interventions to improve mental health in young people (mean age 14–24), delivered by a peer worker with lived experienced of mental health challenges were included. Outcomes related to depression or anxiety were extracted and descriptive synthesis was undertaken due to the heterogeneity of studies. Study quality was rated using the Critical Appraisal Skills Programme; reporting adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Results Nine randomised controlled trials with 2,003 participants were included, with seven undertaken in high income countries. One targeted depression and anxiety, two stigma-distress (any mental disorder), one first episode psychosis, four studies preventing eating disorders and one drug misuse. One study successfully reduced anxiety and depression, another reduced depression only, four reported reductions in negative affect, with the final three measuring, but not having a significant impact on depression. Study quality was rated as ‘good’ overall. Discussion Despite the uptake of youth peer support globally, there is limited evidence from controlled trials of the effect of peer support-related interventions on anxiety and depression. There is some effect on negative affect, especially for university students. Further rigorously designed trials of peer delivered interventions for young people need to be conducted with a focus on understanding the mechanisms of action underpinning peer support.